2016
DOI: 10.1007/s11665-016-2040-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Machinability of Cast Ti-Si Alloys with Varying Si Content

Abstract: This study evaluated the machinability of a series of binary Ti-Si alloys with a goal of developing a titanium alloy with better machinability than commercially pure titanium (c.p. Ti). The alloys were slotted using a milling machine and end mills under four cutting conditions. Machinability was evaluated through cutting force. The experimental results indicate that alloying with Si significantly improved the machinability of c.p. Ti in terms of cutting force under the present cutting conditions. As the Si con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Taking Ti−10Si specimen as an example, the high Ti 5 Si 3 content led to greater cutting forces than those of the unalloyed or low-Si specimens, the structures of which only contained hexagonal α -phase. 31 In this study, the cutting force components decrease with the increase in the Si content for hypereutectic alloys. On one hand, the radial component of cutting force decreases due to the decrease in Young’s modulus with the increase in primary Si particles.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Taking Ti−10Si specimen as an example, the high Ti 5 Si 3 content led to greater cutting forces than those of the unalloyed or low-Si specimens, the structures of which only contained hexagonal α -phase. 31 In this study, the cutting force components decrease with the increase in the Si content for hypereutectic alloys. On one hand, the radial component of cutting force decreases due to the decrease in Young’s modulus with the increase in primary Si particles.…”
Section: Resultsmentioning
confidence: 60%
“…Hsu et al 31 indicated that the chip length decreased with an increase in the concentration of Si, a result which can be explained by the reduced ductility as a result of alloying treatment. The chip manifests more brittle or fragile behaviors as the rising of hardness with increasing Si content, as well as the rising of cutting speed.…”
Section: Introductionmentioning
confidence: 99%
“…The studies revealed that the values of the cutting forces were influenced more by the feed and less by the cutting speed. The influence of the silicon content in the titanium allow on its machinability was considered in [11]. It was found that the presence of silicon significantly increased the machinability of titanium alloys and thus led to a noticeable decrease in the cutting force.…”
Section: Introductionmentioning
confidence: 99%